Influence of summer legumes in rice (Oryza sativa)-wheat (Triticum aestivum) cropping system on soil fertility - SHARMA, S N; PRASAD, R; SINGH, R K (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted for 4 years from 1993-97 at New Delhi to study the effect of Sesbania aculeatagreen manuring and mungbean (Phaseolus radiatus L.) residue incorporation on rice-wheat cropping system. Soil chemical properties studied at the end of 1997 showed that Sesbania green manuring Ilnd mungbean residue incorporation increased soil organic C over summer fallow by 0.105-0.135 %, kjeldahl N by 0.0] % and available P by 5-5.5 kg/ha. Positive effect of fertilizer nitrogen application to rice on Kjeldahl N content of soil was observed in the Sesbania green manured and mungbean residue incorporated plots but not in summer fallow plots. Thus Sesbania green manuring and mungbean residue incorporation practices interact positively with inorganic fertilizer in building-up of soil N.